Nexus of Market Reaction and Persistence of Islamic Bank Profitability in Asia - Putranti, Eti; Budiman, Ahmad; Kusuma, Marhaendra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
This study aims to investigate the reaction of the Islamic stock market to the ability of banks to maintain profitability stability and the moderating role of profit-sharing income in the influence of profitability persistence on Islamic stock prices. Financial report and stock price data from 10 countries in Southeast Asia, South Asia, and the Middle East, with a sample of 67 Islamic banks from 2017 - 2023, with observation data of 469 firm-years, and tested with Moderated Regression Analysis. The test results show that profitability persistence has a positive effect on Islamic stock prices, and profit-sharing income strengthens this effect. The Islamic stock market reacts positively to the ability of bank management to maintain profitability stability over a longer period, and profit-sharing income strengthens the effect of financial performance persistence on the stock prices of Islamic entities. The originality lies in measuring financial performance and testing the moderating role of profit-sharing income. Financial performance is not only measured in a single period but also assessed using profitability persistence as a measure of the bank's ability to maintain financial performance over a long period.